Evaluation of BMT Service Quality Based on SERVQUAL and Maqaṣid al-Shariah: A Case Study of BMT Mandiri Sejahtera Kranji Lamongan - Biyati Ahwarumi; Akhmad Sirojudin Munir (Journal of Management, Accounting, and Administration, 2025)
This study aims to analyze the gap between members' expectations and perceptions of BMT Mandiri Sejahtera Kranji Lamongan services with the SERVQUAL model approach. The research design used a descriptive quantitative approach involving 41 respondents who were selected purposively. The instrument in the form of a Likert questionnaire was analyzed through gap analysis and paired samples t-test. The results showed that there was the largest negative gap in the reliability dimension (−0.2927), while tangibles and responsiveness had positive gaps. Statistically, some service items show significant differences between perceptions and expectations, so the research hypothesis is accepted. This research strengthens the application of SERVQUAL in the context of Islamic microfinance and emphasizes the importance of services that are in accordance with maqāṣid al-sharīʿah. Implicitly, the results of this study are relevant for improving the quality of BMT services and management policies.